Cognitive Bias as a Framework for Analysis of Multimedia Music Reviews (Cases of Pitchfork, Brooklyn Vegan, AllMusic) (Global Journal of Human-Social Science, 2020)
Today, a human being drowns into global, uninterrupted and overweighted streams of information in the network society so we often make decisions irrationally as affected by cognitive biases. However, some genres and formats of modern journalism can use cognitive distortions (heuristics in other words) as a base for that kind of creativity which is acceptable and even necessary in some ways. The article is devoted to the detection of suggestive effects of multimedia music reviews in the focus of heuristics. As a conclusion, a cognitive bias in a media text of this type is regarded as a mean of suggestive expressiveness, not suggestive misinformation.
Keywords: heuristic; music review; cognitive bias; suggestiveness; network society